Assembleia, frugivoria e biologia reprodutiva de morcegos em áreas restauradas - Jacomassa, Fabio Andre Facco [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Faced the loss of habitats, recovery and restoration areas and ecological processes has featured in biodiversity conservation. Thus, it is very important to assess whether the recovered and restored areas are gradually assuming biological properties similar to those of natural environments. These attributes are the return of the species and their mutualism and the reproduction of the species in those areas. In this evaluation bats are a good model, as they are diverse, abundant, have great diversity of use of food resources and habitats, and important ecological function. The general objectives of this thesis were to examine the structure of bat communities (Chapter 1), the diet of frugivorous species (Chapter 2) and the reproductive biology of the species (Chapter 3) in five areas in the state of São Paulo, three of them restored at different ages (areas 1, 2 and 3), a native (4) and a periurban (5). The bats were captured with mist-nets in each area for one year. After captured they were kept in cotton bags to be screened. Feces were collected them coming on plastic under the mist-nets and cotton bags. In trials they were identified, sexed and had their age and reproductive status noted. The seeds of feces were identified using comparisons with reference collections, consultations with specialists and morphometric data. With a monthly effort to 16200 h.m² by area, between April 2012 and March 2013 were 646 catches (50 recaptures) of 18 species belonging to three families. In area 1 were 46 catches (two recaptures) of five species (estimated wealth of Jackknife 2, J2 = 8.5 species and Shannon index H '= 1.56); in area 2 were 173 (26) of 12 species (20.75 and 2.4); in area 3 were 264 (17) of 12 species (19.99 and 2.39); in area 4 were 49 in (two) five (6.75 and 1.27); and in area 5 were 144 catches (five) of tem species (17.99 and 2.23). In 291 feces samples from ten species of bats were found 28,256 seeds of 32 species of plants. Two ...

Diante da perda de habitats, a recuperação e restauração de áreas e processos ecológicos tem destaque na conservação da biodiversidade. Desta forma, é muito importante avaliar se as áreas recuperadas e restauradas estão assumindo gradualmente atributos biológicos semelhantes aos de ambientes naturais. Nesses atributos estão o retorno das espécies e seus mutualismos e a reprodução das espécies presentes nessas áreas. Nessa avaliação os morcegos constituem um grupo zoológico fávorável, pois são diversos, abundantes, possuem grande diversidade de uso de recursos alimentares e de habitats, além de importantes funções ecológicas. Os objetivos gerais desse estudo foram: conhecer a assembleia de morcegos (capítulo 1), a dieta das espécies frugívoras (capítulo 2) e a biologia reprodutiva das espécies (capítulo 3) em cinco áreas no Estado de São Paulo, três delas restauradas com diferentes idades (áreas 1, 2 e 3), uma nativa (4) e outra periurbana (5). Os morcegos foram capturados mensalmente com redes de neblina em cada uma das áreas durante um ano. Após a captura, os animais foram mantidos em sacos de algodão até serem triados. Fezes oriundas do período em que estiveram presos nas redes foram coletadas de plásticos dispostos sob as redes, bem como dos sacos de algodão. Nas triagens os morcegos foram identificados, sexados e tiveram sua faixa etária e estado reprodutivo anotados. As sementes das fezes foram identificadas usando-se comparações com coleções de referência, consultas a especialistas e dados morfométricos. Com um esforço mensal de 16200 h.m² por área, entre abril de 2012 e março de 2013 foram 647 capturas (50 recapturas) de 18 espécies pertencentes a três famílias. Na área 1 foram 46 capturas (duas recapturas) de cinco espécies (estimativa de riqueza Jackknife 2, J2 = 8,5 espécies; Chao 1, C1 = 5 espécies e índice de Shannon H' = 1,56); na 2 foram 173 (26) de 12 (20,75; 15,33 e...
Keywords: Bats; Morcego; Sementes - Disseminação; Mutualismo; Recuperação ecológica; Especies